2008
DOI: 10.1002/ejic.200700808
|View full text |Cite
|
Sign up to set email alerts
|

New Coordination Modes of L‐Ascorbic Acid and Dehydro‐L‐ascorbic Acid as Dianionic Chelating Ligand for Platinum

Abstract: A variety of coordination modes of L-ascorbic acid as an anionic bidentate ligand has been exploited to prepare platinum(II) complexes 1-7 that contain phosphanes or R,R-dach (1R,2R-diaminocyclohexane) as neutral ligands in which O2, O3, O5, O6 and C2 act as anionic donating functionalities. An alternative synthetic route to known O2,O3 complexes is proposed, and their solubility in water has been enhanced by introducing PTA (1,3,5-triaza-7-phosphaadamantane) as a neutral ligand. A new coordination mode of asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Comparing the structures of A and B1 shows that an oxygen atom O(2) is inserted in each Pt−C bond. The Pt−O(2) bond (1.996(4) Å) is slightly shorter than the one in a reported Pt II -ketal complex (2.027(3) Å) . The Pt II ion displays a severely distorted square planar geometry where the P−Pt−P angle facing the O(2) is 155.79(6)° only.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Comparing the structures of A and B1 shows that an oxygen atom O(2) is inserted in each Pt−C bond. The Pt−O(2) bond (1.996(4) Å) is slightly shorter than the one in a reported Pt II -ketal complex (2.027(3) Å) . The Pt II ion displays a severely distorted square planar geometry where the P−Pt−P angle facing the O(2) is 155.79(6)° only.…”
Section: Resultsmentioning
confidence: 67%
“…The Pt-O(2) bond (1.996(4) A ˚) is slightly shorter than the one in a reported Pt II -ketal complex (2.027(3) A ˚). 20 The Pt II ion displays a severely distorted square planar geometry where the P-Pt-P angle facing the O(2) is 155.79(6)°o nly.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the Pt(II) complex can undergo facile complexation with AA and DHA. [45][46][47] The new spectral band at 300 nm for the reaction mixture could be due to the PtCl presence of DHA does not undergo galvanic displacement reaction with the Pd nanoparticles. The absence of such a reaction could be due to the complexation of Pt(II) with DHA.…”
Section: Resultsmentioning
confidence: 99%
“…The 31 P NMR spectrum of 4 shows two doublets with satellites at 11.91 ppm (3891 Hz) and 8.73 ppm (3376 Hz) due to two phosphorus atoms with different O‐donors in the trans positions. Comparing the 1 J Pt,P value with the value for phosphorus trans to a carboxylate group, for example, 3770 Hz for [Pt(oxalato)(PPh 3 ) 2 ]12 and 3300–3500 Hz for PPh 3 (diolato)Pt,3 we assign the signal at 11.91 ppm to the phosphorus trans to the carboxylate group.…”
Section: Resultsmentioning
confidence: 99%
“…A few years ago it was reported that L ‐ascorbic acid, a vitamin provided with specific transporters across the blood‐brain barrier, can be exploited as a carrier for drugs for CNS pathologies 2. We considered the possibility of extending this strategy to platinum drugs, and therefore we are currently investigating the coordination modes to platinum of L ‐ascorbic acid itself, of its oxidated form (dehydroascorbic acid, DHA) and of some derivatives, like O ‐protected forms 3…”
Section: Introductionmentioning
confidence: 99%